The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5012/bkcs.2012.33.5.1566
|View full text |Cite
|
Sign up to set email alerts
|

Composite of Indium and Polysorbate 20 as Inhibitor for Zinc Corrosion in Alkaline Solution

Abstract: The combined use of indium and polysorbate 20 (Tween 20) was considered as a new inhibition technique for zinc corrosion. Zn and Zn-In alloy coatings were prepared by electrodeposition and their morphology and composition were characterized by scanning electron microscopy (SEM) and inductively coupled plasma atomic emission spectrometry (ICP-AES). The corrosion inhibition effect of indium and Tween 20 on zinc was investigated by polarization curves and electrochemical impedance spectroscopy (EIS). The corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…1 shows the IR spectra for SSL, Tween 20 and κ-carrageenan. Table 2 shows their characteristic absorption bands, allocated according to available sources [1] , [2] , [3] , [4] , [5] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…1 shows the IR spectra for SSL, Tween 20 and κ-carrageenan. Table 2 shows their characteristic absorption bands, allocated according to available sources [1] , [2] , [3] , [4] , [5] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…[38] Indium is known to hinder the hydrogen evolution reaction when this metal is present on the negative electrode surface. [39][40][41][42] Indium is non-toxic and environmentally friendly, although expensive. Therefore, the indium content in the electrode formulation must be minimized in order to stick with the requirements of feasible ZIBs prototypes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our group has recently developed an optimized powder electrode consisting of bismuth and indium particles acting as a substrate for achieving an efficient electrodeposition of zinc from diluted electrolytes [38] . Indium is known to hinder the hydrogen evolution reaction when this metal is present on the negative electrode surface [39–42] . Indium is non‐toxic and environmentally friendly, although expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some organic agents have been added to the electrolyte to deposit a flat Zn‐based film composed of smaller grains . Organic additives also can influence the electrochemical behavior during electrodeposition, such as the grain size, chemical composition, and anticorrosion . For instance, de Almeida et al reported electrodeposited Cu–Zn alloys on steel using alkaline electrolytes with various concentrations of ethylenediaminetetraacetic acid (EDTA) .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the grain size of the Zn alloy decreased with increasing EDTA concentration in the electrolyte . Li reported that polysorbate 20 (Tween 20) could inhibit Zn corrosion in a KOH solution . Torrent‐Burgues reported the electrodepostion of Zn using tartaric acid .…”
Section: Introductionmentioning
confidence: 99%